1995
DOI: 10.1152/ajpheart.1995.268.3.h1106
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in liver hemodynamics in an intact porcine model of endotoxin shock

Abstract: Septic shock decreases preload, increases splanchnic blood pooling and edema formation, and induces hepatic dysfunction. We hypothesized that the hemodynamic effects of endotoxemic shock on the portal venous (PV) and hepatic arterial (HA) vascular beds contribute to this picture. Multipoint pressure-flow relationships were generated to evaluate the slope (resistance or conductance) and effective back pressure (Pback) in each bed in an intact porcine model of endotoxemia. Slope and Pback were determined during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 0 publications
2
35
2
Order By: Relevance
“…In addition, there were no significant changes in heart rate. Thus, it is possible that the reduction in cardiac output observed in animals treated with LPS in the present investigation was the result of a reduction in venous return (2,21). Moreover, it is possible that treatment with rolipram and dexamethasone augmented venous return, thereby resulting in the maintenance of cardiac output in LPS-treated rats.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, there were no significant changes in heart rate. Thus, it is possible that the reduction in cardiac output observed in animals treated with LPS in the present investigation was the result of a reduction in venous return (2,21). Moreover, it is possible that treatment with rolipram and dexamethasone augmented venous return, thereby resulting in the maintenance of cardiac output in LPS-treated rats.…”
Section: Discussionmentioning
confidence: 71%
“…Reportedly, treatment of rats with LPS did not appear to significantly affect arterial resistance or resistance to venous return (2). However, endotoxic shock has been reported to lead to an impairment of portal venous flow with increased portal venous resistance causing an increase in splanchnic blood pooling and subsequent decrease in venous return and thus cardiac output in anesthetized pigs (21). Taken together, the evidence would suggest that the reduction in cardiac output in endotoxic shock is, in part, due to a reduction in venomotor tone.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we found a decreased but still detectable HABR after 18 h of endotoxin infusion, which did not further deteriorate during continued endotoxin infusion. It has been shown that hepatic arterial resistance is increased for a given portal venous flow after several hours of endotoxin infusion (1). Lipopolysaccharide infusion decreases mRNA levels of constitutive nitric oxide synthase in liver tissue (37), and administration of the nitric oxide donor sodium nitroprusside during endotoxemia is able to both improve hepatic arterial flow and restore the autoregulatory response of the hepatic artery following reduction of hepatic blood flow (15,37).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that endo toxin induces a dysfunction of the hepatic arterial buffer response [29,30]. So far the mechanisms have been partly unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…endotox emia) have the potential to abolish or reduce this effect and instead direct vasoconstriction at the underlying smooth muscle [32,33], This may explain that hepatic arterial resis tance tended to increase during edotoxin infu sion, although the values did not reach statis tical significance. Other investigators report conflicting results on this point, probably re lated to the duration of endotoxemia [14,30,34], The subsequent injection of the nonselective NOS inhibitor L-NAME nearly dou bled hepatic arterial resistance, indicating that the endogenous local production of NO was maintained at a sufficient level to have considerable effects upon hepatic circulation. It may be anticipated that suppression of endothelial NO production in this and similar situations will aggravate liver injury by reduc ing and perturbing microcirculation.…”
Section: Discussionmentioning
confidence: 99%